Fluorescent probe for specific detection of cysteine in the lipid dense region of cells - Ali, Firoj; Anila, H. A.; Taye, Nandaraj; Gonnade, Rajesh G.; Chattopadhyay, Samit; Das, Amitava (Chemical Communications, 2015)
A new cysteine (Cys) specific chemodosimetric reagent (ER-F) is used in imaging of endogenous Cys localized in the lipid dense region of the live Hct116 cells and the release of Cys within HepG2 cells from a drug following a biochemical transformation. A silica surface, modified with ER-F, could be used for quantitative estimation of Cys present in aqueous solution (pH 7.2) and in a human blood plasma (HBP).